2010
DOI: 10.1016/j.matlet.2010.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-electric coupling in multiferroic La0.8Bi0.2Fe0.7Mn0.3O3 ceramic

Abstract: We present here the structural, electrical, magnetic and magneto-electric properties of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…6 shows the change in the real part of the relative dielectric permittivity of the nanostructural BTZF composites at 1 kHz as a function of magnetic eld H dc and measured at room temperature. Clearly, the capacitance decreases with increasing applied magnetic eld (negative value of MC) and a similar behavior is also observed by Anjum et al 55 for their MF system. The value of MC at H dc ¼ 3 kOe is 2.84, 1.24, 0.78, 1.42 and 1.12%, respectively, calculated for BTZF2575, BTZF3565, BTZF4555, BTZF5050 and BTZF7525 composites.…”
Section: Resultssupporting
confidence: 86%
“…6 shows the change in the real part of the relative dielectric permittivity of the nanostructural BTZF composites at 1 kHz as a function of magnetic eld H dc and measured at room temperature. Clearly, the capacitance decreases with increasing applied magnetic eld (negative value of MC) and a similar behavior is also observed by Anjum et al 55 for their MF system. The value of MC at H dc ¼ 3 kOe is 2.84, 1.24, 0.78, 1.42 and 1.12%, respectively, calculated for BTZF2575, BTZF3565, BTZF4555, BTZF5050 and BTZF7525 composites.…”
Section: Resultssupporting
confidence: 86%
“…Idress et al reported that the CDC behavior in LaFeO 3 is an extrinsic effect due to Maxwell-Wagner relaxation in the system [19]. Currently, the existing dielectric investigations on this material were concentrated on the doped LaFeO 3 system and mainly focused on the magnetocapacitance effect [20][21][22][23]. The dielectric properties of pure LaFeO 3 are far from well characterization.…”
Section: Introductionmentioning
confidence: 99%
“…). Clearly, the capacitance decreases with increasing H dc (negative value of MC) . This negative value of MC at H dc = 3 kOe and frequency 1 kHz (2.27% and 1.81%), 10 kHz (1.47% and 0.86%), and 10 MHz (0.70% and 0.39%), respectively, measured for BFTO:Ce and BFTO:La.…”
Section: Resultsmentioning
confidence: 73%